Forming a three-dimensional porous organic network via solid-state explosion of organic single crystals. Issue 1 (December 2017) - Bae, Seo-Yoon; Kim, Dongwook; Shin, Dongbin; Mahmood, Javeed; Jeon, In-Yup; Jung, Sun-Min; Shin, Sun-Hee; Kim, Seok-Jin; Park, Noejung; Lah, Myoung; Baek, Jong-Beom
Abstract Solid-state reaction of organic molecules holds a considerable advantage over liquid-phase processes in the manufacturing industry. However, the research progress in exploring this benefit is largely staggering, which leaves few liquid-phase systems to work with. Here, we show a synthetic protocol for the formation of a three-dimensional porous organic network via solid-state explosion of organic single crystals. The explosive reaction is realized by the Bergman reaction (cycloaromatization) of three enediyne groups on 2, 3, 6, 7, 14, 15-hexaethynyl-9, 10-dihydro-9, 10-[1, 2]benzenoanthracene. The origin of the explosion is systematically studied using single-crystal X-ray diffraction and differential scanning calorimetry, along with high-speed camera and density functional theory calculations. The results suggest that the solid-state explosion is triggered by an abrupt change in lattice energy induced by release of primer molecules in the 2, 3, 6, 7, 14, 15-hexaethynyl-9, 10-dihydro-9, 10-[1, 2]benzenoanthracene crystal lattice. Porous organic networks are of great fundamental and technological interest. Here, the authors synthesize a three-dimensional porous organic network with high specific surface area via a solid-state explosive reaction of hexaethynyl triptycene single crystals containing primer molecules.